Analyzing Student Perceptions of Gamified Assessment: A Case Study of Quizizz in Higher Education English Classes - Engelina Salainti; Gabriella Alleid Dian Baureh (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
A higher education landscape that has been digitized encourages the need for an assessment method that is more interesting and effective. This background is in contrast to the classic problems, where the traditional assessment method often triggers anxiety and the lack of students’ engagement. As a solution, gamification, especially through platforms such as Quizizz, was proposed to transform the assessment experience. However, empirical research that has students’ specific perceptions in the context of English classes in higher education institutions is still limited. To address this gap, mixed-methods research with a case study approach is conducted. Data gathered through a survey questionnaire (quantitative) covering cognitive, conative, and affective aspects of perceptions, and semi-structured interviews (qualitative) from the students who use Quizizz. The key findings revealed that overall, the students’ perceptions of Quizizz were positive. This study emphasized that Quizizz is an effective assessment tool and is liked in the context of English class in higher education institutions. This study not only provides practical insight to educators on implementing more engaging assessments but also contributes to the theoretical understanding of the impact of gamification on students’ learning perceptions.